PEMBUATAN BUKU SAKU SUBMATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA - Mitalia, Mitalia; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the feasibility of pocket book as a learning media on submaterial utilization of biodiversity in Indonesia for Xth class high school students. The research method was descriptive with survey form. The pocket book was validated using validation instrument sheet. The pocket book feasibility test was performed by five validators that include an assessment of aspects of formatting, content, language, and attractiveness. From all aspects of the value indication CVR and CVI respective of 0.99. It can be concluded that the pocket book was valid and proper to be used as a media of instruction on submateri utilization of biodiversity of Indonesia Xth class high school students.Â Keywords: Pocket Book, Feasibility, Submaterial Utilization of Indonesiaâ€™s Biodiversity